1982
DOI: 10.1148/radiology.144.4.7111740
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of the normal pediatric gallbladder and biliary tract.

Abstract: Fifty-one pediatric patients (range, 1 mo. to 16 yr.), all of whom had normal clinical findings and laboratory data pertaining to the gallbladder and biliary tract, were examined by ultrasound. Scans showed a gradual increase in the size of the gallbladder with age; only one patient had a gallbladder diameter greater than 3.5 cm or a length greater than 7.5 cm. Wall thickness could be measured in 45 patients and was never more than 3 mm. The lumen of the common hepatic duct gradually increased with age but was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 0 publications
2
23
1
Order By: Relevance
“…A wall thickness greater than 3 mm was considered abnormal [23]. Presence or absence of gallstones was noted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wall thickness greater than 3 mm was considered abnormal [23]. Presence or absence of gallstones was noted.…”
Section: Methodsmentioning
confidence: 99%
“…Presence or absence of gallstones was noted. The diameter of the common bile duct was assessed and considered as normal if smaller than 4 mm [23]. Spleen size was regarded normal if the spleen did not extend over the inferior margin of the left kidney [24].…”
Section: Methodsmentioning
confidence: 99%
“…Recent attempts at establishing normal and abnormal ultrasonographic measurements should be helpful in that respect [16,17]. Caroll et al, in their study of the neonatal biliary system using real time ultrasound, found no statistically significant difference between the lengths of normal gallbladders and those felt as upper quadrant masses but the gallbladder width was significantly increased in those with masses [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is also valuable in detecting stones or sludge in the gallbladder and bile ducts and in evaluating the size of these ducts [6,16,17]. However, ultrasonography has its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Photo courtesy of Dr. Shaun Steigman right upper quadrant/epigastric pain along with a transabdominal ultrasound depicting gallstones or sludge, gallbladder wall thickening, an enlarged/distended gallbladder, pericholecystic fl uid, and/or a sonographic Murphy's sign confi rms or at least solidifi es the diagnosis. Normal gallbladder wall thickness in children under 16 years of age is ≤3 mm [ 25 ]. The positive predictive value of ultrasound in pediatric cholecystitis is reported to be 67-87 % [ 26 ].…”
Section: Acute Cholecystitismentioning
confidence: 99%